2021
DOI: 10.1111/acps.13359
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and pooled, patient‐level analysis of predictors of mortality in neuroleptic malignant syndrome

Abstract: Objective Neuroleptic malignant syndrome (NMS) is a potentially fatal, idiosyncratic reaction to antipsychotics. Due to low incidence of NMS, research on risk factors of mortality associated with NMS is limited. Methods Two authors independently searched Medline/Embase/Cochrane/CINAHL/PsychINFO databases for case reports with author‐defined NMS published in English until 05/30/2020. Demographic, clinical, treatment, and outcome data were independently extracted following PRISMA guidelines. NMS severity was rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 52 publications
0
31
0
1
Order By: Relevance
“…The elderly should be extra careful when using APDs as well. Research performed by Daniel showed that older age is a risk factor for death from the neuroleptic malignant syndrome, which is a potentially fatal idiosyncratic reaction caused by APDs ( Guinart et al, 2021 ). There may be two reasons for the lower proportion of severe ADR in high-level hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The elderly should be extra careful when using APDs as well. Research performed by Daniel showed that older age is a risk factor for death from the neuroleptic malignant syndrome, which is a potentially fatal idiosyncratic reaction caused by APDs ( Guinart et al, 2021 ). There may be two reasons for the lower proportion of severe ADR in high-level hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In general, in this population, antipsychotics can also increase the risk of NMS and can contribute to the development or worsening of catatonic symptoms[ 182 , 183 ]. Moreover, the NMS risk of poor outcome and mortality is associated with older age[ 184 ]. Some authors have recommended antipsychotic discontinuation during the acute phase of catatonia and to reinitiate treatment once catatonia is in remission[ 5 , 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the fact that treated patients showed higher mortality compared with NMS cases not receiving dantrolene suggests it may be ineffective or worse, the effectiveness of dantrolene in NMS cannot be addressed by our data because groups were neither randomized, controlled, blinded, nor matched [ 42 ]. For example, concurrent sepsis or other comorbidities and symptom severity have been identified as significant predictors of mortality and response in NMS in previous studies [ 38 , 42 , 48 , 50 , 51 ]. Evidence on the efficacy of dantrolene for NMS is inconclusive pending studies using standardized diagnostic criteria that also control for co-morbidities and severity of symptoms [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%